Factors Affecting the Performance of Islamic Banking Employees - Lestari, Septiyani Priska Putri; Guritno, Agung (Velocity: Journal of Sharia Finance and Banking, 2021)
This study aims to see how remuneration, competence, and organizational culture affect employee performance at Bank Syariah Indonesia Semarang Branch. This is a quantitative analysis with 50 employees of Bank Syariah Indonesia Semarang Branch participated. The data were processed with the SPSS version 20 application tool. Instrument tests, classical assumption tests, statistical tests, and MRA tests are all included in this study's analysis. The T-test results show that remuneration has no significant impact on employee performance, integrity has a positive and significant impact on employee performance, and motivation has no impact on employee performance. Organizational Culture variables moderate / reinforce the relationship between Reward for Employee Performance, Competence, and Employee Performance, and Motivation and Employee Performance. The implications of the study are, the management should give more attention to the remuneration and motivation factors to enhance employee performance.This study aims to see how remuneration, competence, and organizational culture affect employee performance at Bank Syariah Indonesia Semarang Branch. This is a quantitative analysis with 50 employees of Bank Syariah Indonesia Semarang Branch participated. The data were processed with the SPSS version 20 application tool. Instrument tests, classical assumption tests, statistical tests, and MRA tests are all included in this study's analysis. The T-test results show that remuneration has no significant impact on employee performance, integrity has a positive and significant impact on employee performance, and motivation has no impact on employee performance. Organizational Culture variables moderate / reinforce the relationship between Reward for Employee Performance, Competence, and Employee Performance, and Motivation and Employee Performance. The implications of the study are, the management should give more attention to the remuneration and motivation factors to enhance employee performance.